Environment for the Evaluation of Hybrid (Classical-Quantum) Systems Analyzability [Focus: Quantum Software and Its Engineering] - Diaz-Munoz, Ana; Verdugo, Javier; Rodriguez, Moises; Cruz-Lemus, Jose A.; Martinez-Gasca, Rafael; Piattini, Mario (IEEE software, 2025)
We present a methodological and technological environment consisting of a set of properties and metrics and automated tools that allow evaluations on the analyzability of hybrid software. Furthermore, our proposal has been applied to an actual case of a hybrid product, demonstrating its usefulness.